Coronavirus disease 2019 vaccine acceptance and perceived barriers among university students in northeast Ethiopia: A cross-sectional study - Birhan Tsegaw Taye; Fetene Kasahun Amogne; Tesfanesh Lemma Demisse; Mulualem Silesh Zerihun; Tebabere Moltot Kitaw; Agumas Eskezia Tiguh; Muhabaw Shumye Mihret; Azmeraw Ambachew Kebede (Elsevier, 2021)
Background: Universities are places where students live and study in close contact to each other. Nowadays, the foundations of this particular group have been affected significantly by the rapid spread of the coronavirus disease 2019. The severity of the COVID-19 pandemic has demanded the emergency use of COVID-19 vaccines. However, there is still limited evidence in COVID-19 vaccine acceptability and perceived barriers among some subgroups, including university students. This study aimed to assess vaccine acceptance, associated factors, and perceived barriers among university students, Ethiopia. Methods: A cross-sectional study was conducted in January 2021 at Debre Berhan University among 423 students. The participants were selected using simple random sampling technique. A semi-structured, pretested, and self-administered questionnaire was used to collect the data. Multivariable logistic-regression model was fitted to identify factors associated with vaccine acceptance. An adjusted odds ratio with 95% confidence interval and its p-value of ≤0.05 was used to declare significant association. Results: The proportion of the COVID-19 vaccine acceptance was 69.3% (95% CI: 65, 74). Being knowledgeable (AOR: 2.43, CI: 1.57, 3.77), being a health science student (AOR: 2.25, CI: 1.43, 3.54), and being in a family practicing COVID-19 prevention (AOR: 1.73, CI: 1.06, 2.81) were found to be factors associated with COVID-19 vaccine acceptance. Conclusion: Though, this study found a 69.3% acceptance of COVID-19 vaccine, there were noticeable perceived barriers and related factors in vaccine acceptance hesitancy. Thus, health education and communication regarding the vaccine are very crucial to alleviate the identified barriers.